Assessing intermodal freight transport scenarios bringing the perspective of key stakeholders - Prata, J. (2017)
This paper extends the previous R&D project on the evaluation of intermodal freight transport scenarios (seamless multimodal logistic chains) centered in the Port of Sines in Portugal where a set of alternative investment options were compared: (i) maritime – maritime (short-sea-shipping); (ii) maritime-road; (iii) maritime-rail; (iv) maritime-rail-air. This paper aims to bring the perspective of key stakeholders gathered in a specific workshop and assesses the impact of their views in the evaluation of options. The impact analysis focuses on most critical operational and environmental variables, namely shipping speed and CO2 emissions.